Conditions of Submicrocrack Formation During Shock-Wave Treatment of Metals - Didyk, R.P. (Видавничий дім "Академперіодика" НАН України, 2006)
The formation of submicrocracks located at a quite substantial distance from the source of disturbance, under the action of powerful shock waves has been observed and studied by electron microscopy. The
ultimate parameters of the shock waves (pressure, deformation degree) at which the submicrocrack formation
is eliminated, have been determined theoretically and confirmed experimentally. Effective means for the prevention of the microfaults formation in the process of ex
plosive hardening treatment of metals have been
developed. За допомогою електронної мікроскопії вивчене утворення субмікротріщин, розташованих
на певній відстані від джерела під дією потужної ударної хвилі. Оптимальні параметри ударної хвилі
(тиск, ступінь деформації), при яких знижується утворення субмікротріщин, визначені теоретично та
підтверджені експериментально. Розроблені ефективні засоби запобігання мікроруйнувань у процесі
зміцнення металів вибухом. С помощью электронной микроскопии изучено образование субмикротрещин, рас
положенных на определенном расстоянии от источника под действием мощной ударной волны. Оптимальные параметры ударной волны (давление, степень деформации), при которых снижается образование субмикротрещин, определены теоретически и подтверждены экспериментально. Разработаны
эффективные средства предотвращения микроразрушений в процессе упрочнения металлов взрывом.